Antibiotic resistance associated lactic acid cross tolerance in Shiga-toxin producing E. coli - Oguadinma, Ikechukwu; Mishra, Abhinav; Dev Kumar, Govindaraj (Frontiers in Microbiology, 2023)
The occurrence of antibiotic resistant (ABR) bacteria in the food chain is a growing public health challenge. We evaluated sanitizer cross-tolerance among antibiotic resistant E. coli O157:H7 and non-O157:H7 STEC serogroups. Sanitizer tolerance in Shiga-toxin producing E. coli (STEC) could be a public health concern as mitigation strategies against the pathogen might be undermined. Resistance to ampicillin and streptomycin were evolved in E. coli serogroups: O157:H7 H1730, O157:H7 43895, O121:H19 and O26:H11. ABR profiles were evolved chromosomally through incremental exposure to ampicillin (amp C) and streptomycin (strep C). Transformation using a plasmid was performed to confer resistance to ampicillin to generate amp P strep C. The minimum inhibitory concentration (MIC) of lactic acid for all strains evaluated was 0.375 % v/v. Analysis of bacterial growth parameters in tryptic soy broth amended with 0.0625 % v/v, 0.125 % v/v, and 0.25 % v/v (subMIC) lactic acid indicated that growth correlated positively with the lag phase duration, and negatively with both the maximum growth rate and change in population density for all strains evaluated except for the highly tolerant variant- O157:H7 amp P strep C. Strains O121 NR (non-ABR), O121 amp C, O121 amp P strep C, O157:H7 H1730 amp C and O157:H7 H1730 amp P strep C were not inactivated after exposure to 1 % and 2.5 % v/v lactic acid for 300 s. No recovery of cells was observed after the strains were exposed to 5 % v/v lactic acid for 300 s. ABR strains O157:H7 H1730 amp C and O157: H7 H1730 amp P strep C demonstrated a high tolerance to lactic acid (P ≤ 0.05). The results indicate that ABR in some STEC serogroups may improve tolerance to lactic acid. Increased tolerance may be discerned by evaluating growth parameters of bacteria in presence of sub-MIC levels of lactic acid.